Role of FRAX in the Evaluation of Osteoporosis in Patients with Chronic Obstructive Pulmonary Disease - Onur Yazıcı; Şenay Demir Yazıcı (Galenos Yayinevi, 2021)
Objective:The incidence of osteoporosis increased in patients with chronic obstructive pulmonary disease (COPD), and fractures due to osteoporosis are a significant cause of morbidity. Thus, risk assessment and taking necessary precautions are essential in these patients. This study aimed to assess the fracture risk of patients with COPD scanned with dual-energy X-ray absorptiometry (DXA) using the fracture risk assessment tool (FRAX) and to identify their treatment status.Materials and Methods:Patients who presented to the Physical Therapy Outpatient Clinic of Aydın Atatürk State Hospital and diagnosed with COPD between January 2014 and January 2019 were included in the study. Results of DXA and pulmonary function test performed within the last year were recorded. According to the DXA results, patients were divided into osteoporotic, osteopaenic and normal groups. Patients were also classified into group A, B, C and D according to the Global Initiative for Chronic Obstructive Lung Disease classification. FRAX values were calculated using an online calculator.Results:Ninety-five patients with COPD were enrolled in the study. According to their DXA values, 39 (41.1%), 41 (43.2%) and 15 (15.8%) patients were allocated in the osteoporotic, osteopaenic and normal groups, respectively. The 10-year major osteoporotic and hip fracture risks, calculated using FRAX, was the highest in the osteoporotic group, followed by the osteopaenic group (p<0.001 and p<0.001, respectively). Thirty-six patients (92.3%) in the osteoporotic group received medical treatment for osteoporosis, whereas only 13 (31.7%) patients in the osteopaenic group received medical treatment. FRAX assessment revealed that both major osteoporotic and hip fracture risks were higher in groups C and D (p=0.002 and p=0.002, respectively).Conclusion:All patients with COPD, particularly those in groups C and D, should be assessed with both DXA and FRAX, regarding osteoporosis and fracture risks, and preventive measures/treatment should be planned when required.